Functional Outcome of Intradural Extramedullary Spinal Tumors after Surgical Resection - Sharma, Gopal R; Jha, Rajiv; Poudel, Prakash; Khadka, Nilam; Adhikari, Dhurba R; Bista, Prakash (Nepal Journal of Neuroscience, 2016)
Intradural extramedullary (IDEM) spinal tumors account about 40% of all intraspinal tumors and mainly represented by nerve sheath tumors and meningiomas. These two tumors represent about 55% of IDEM tumors and other rare tumors are dermoid, epidermoid, lipomas, metastatic tumors, paragangliomas etc. Technical advances in imaging techniques, MRI and surgical procedures have brought about excellent clinical results of IDEM tumors after surgery in last two decades. However, a small percentage of patients still present poor postoperative neurological outcome due to delayed in diagnosis and surgical intervention, severity of preoperative neurological defi cits and adverse pathology. The aim of this study is to analyze and discuss about the surgical outcome of 65 IDEM tumors operated in twelve years’ period. This is a retrospective study of 65 patients who were operated for IDEM tumors, between 1999 and 2012 in Department of Neurosurgery. One patient who had IDEM arteriovenous malformation was excluded from the study. Neurological outcome was scaled by McCormick’s grading. Follow up period ranged for 5 years to 17 years. After the clinical evaluation, all the patients suspected of having spinal tumors were subjected for MRI with Gadolinium enhancement of presumed level of spine based on neurological findings. Total excision of all IDEM tumors was performed using operating microscope. No intraoperative neurophysiological monitoring was used. There were 40 male and 25 female and age ranged from 10 to 80 years. Most common IDEM tumors were nerve sheath tumors (44), meningiomas (13), hydatid cyst (2), dermoid/epidermoid (2), arachnoid cyst (2) and n were thoracic, cervical and lumbar spines.Total tumor excision was performed in all cases. Post operative Complications rate was 12.3% (7) and common complications included were CSF Leak (5), wound infection (2), meningitis (1). There was no surgery related mortality. Postoperatively 60 patients had improved neurological status, 5 patients had stable neurology. There was no postoperative neurological deterioration. On followed up period 2 patients showed features of recurrence of tumor in 5 years’ period and underwent resurgical treatment. Those two patients with recurrent tumors were nerve sheath tumors. Majority of IDEM tumors are benign and total cure is possible in almost all cases if tumor is excised totally. Excellent neurological recovery has been observed in more than 95% of cases. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 73-80